Surfaces (Technology) Surface preparation Coating processes Tungsten carbide-cobalt alloys - Wong, Kah Yan (2021)
Within electronics industry, flexible printed circuits (FPC) are compiled in stacks to achieve smaller sizes and higher component density. The architecture size of a computer processor has been shrunk from 10 µm to 7 nm from year 1971 to 2020. In order to meet the market expectation, manufacturers have to decrease the device size while maintain the product performance. However, the shrinking of device could potentially lead to higher failure rates and lower production yields. If the process is not optimise, the yields of the process will become lower as the device size shrink year by year. Therefore, the optimisation of the copper via filling process plays a very crucial role in manufacturing quality and defectless FPC. In this research, the effects of the electroplating copper via filling parameters (current density (Id), fluid flow rate (Q) and filling time (tf)) on the filling characteristics of copper filled micro via (surface thickness, dimple depth and via filling ratio) were investigated and optimized in the study. A Box-Behnken design response surface methodology (BBD RSM) matrix created by Minitab software was used to determine the parameter effects and the optimum parameters of this study. The process was carried out by using the copper via filing machine that was customize for the experiment whereas the electrolytes used in the experiment were according to the industry standard. The findings yielded that current density was significant to surface thickness, whereas fluid flow rate was significant to the dimple depth and via filling ratio. Apart from that, the optimum parameter to achieve thin surface thickness, low dimple depth and high via filling ratio were Id = 1.5 A/dm2, Q = 25 m3/h and tf = 60 minutes. The main mechanism affecting the via filling characteristics using fluid flow rate was changing the mass transfer of the electrolyte, whereas filling time and current density affected the filling characteristic by controlling the amount of electron supply to the cathode.